2017
DOI: 10.3945/ajcn.116.147553
|View full text |Cite
|
Sign up to set email alerts
|

Validation of spot urine in predicting 24-h sodium excretion at the individual level ,

Abstract: Background: Evidence for the effect of dietary sodium intake on the risk of cardiovascular disease has been controversial. One of the main explanations for the conflicting results lies in the great variability associated with measurement methods for sodium intake. Spot urine collection is a convenient method commonly used for sodium estimation, but its validity for predicting 24-h urinary sodium excretion at the individual level has not been well evaluated among the general population. Objective: The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 25 publications
8
48
3
Order By: Relevance
“…Although the Tanaka formula showed the best performance in predicting 24-hUNa excretion at population level, the misclassification rates at individual level were more than 60%. These results were consistent with previous studies conducted in Chinese [17,20] and in US adults with chronic kidney disease [25]. It indicated that these six formulas might be inappropriate to estimate 24-hUNa excretion at individual level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the Tanaka formula showed the best performance in predicting 24-hUNa excretion at population level, the misclassification rates at individual level were more than 60%. These results were consistent with previous studies conducted in Chinese [17,20] and in US adults with chronic kidney disease [25]. It indicated that these six formulas might be inappropriate to estimate 24-hUNa excretion at individual level.…”
Section: Discussionsupporting
confidence: 91%
“…Two previous studies reported that Tanaka performed well to predict mean population 24-hUNa excretion in both Chinese adults [16] and young adolescents [17], which was in conformance with our study. Nevertheless, other previous studies in Chinese adults found that the Kawasaki formula showed the lowest bias compared to Tanaka and INTERSALT formulas in both general [18][19][20][21] and hypertensive populations [22]. However, the Kawasaki formula performed worst among the six equations in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…1,7,48 Similar conclusions were also drawn in studies that used P30 or P40 as the measure of individual accuracy of the evaluated formulas. 19,24,49 Regarding the relative value of the compared equations, the available data also come mostly from studies performed in the general population. The estimates of 24hUNa excretion using the Kawasaki and Tanaka equations were found to be inadequate in non-Asian populations.…”
Section: Statistical Approaches To Comparing Measured and Estimated 2mentioning
confidence: 99%
“…While 24-h urine collection is regarded as a proper method for assessing 24-h urinary sodium excretion and dietary sodium intake, it is often unfeasible in clinical practice due to high participant burden [10,11]. To overcome its drawbacks, several mathematical estimation models, including the Kawasaki, Tanaka, and Mage methods, have been introduced to estimate dietary sodium intake from spot urine samples [12,13]. Nevertheless, the validity of these estimated 24-h urinary sodium excretion (e24hUNaE) methods in relation to arterial BP remains to be evaluated.…”
Section: Introductionmentioning
confidence: 99%